Báo cáo tóm tắt điều chỉnh quy hoạch chung Thủ đô Hà Nội đến năm 2045, tầm nhìn đến năm 2065 - Bộ Xây dựng (2024)
Toàn văn Báo cáo tóm tắt điều chỉnh quy hoạch chung Thủ đô Hà Nội đến năm 2045, tầm nhìn đến năm 2065.